Handbook of thermoluminescence - Furetta, C., 1937- (World Scientific Pub. Co., 2010)
This second edition of the Handbook of Thermoluminescence enlarges on all the subjects which were treated in the first edition and adds further arguments, including the theory of thermoluminescent dose measurement, several examples concerning the kinetics parameters determination using various methods such as peak shape, isothermal decay, and so on. A special section is devoted to food irradiation, an important subject at the present time, and to the thermoluminescent characterization of the minerals extracted from the irradiated food. Another new section is devoted to the thermoluminescent phosphors and their main characteristics. The analytical treatments of the various thermoluminescent models are fully developed. As in the first edition, the arguments are given in alphabetical order to ease research. This second edition therefore aims to provide real practical support for researchers, students and personnel involved in radiation protection services, as well as in medical applications.